Prevalence of vulvovaginal candidiasis among pregnant women in the Ho municipality, Ghana: species identification and antifungal susceptibility of Candida isolates - Sayanika Devi Waikhom; Innocent Afeke; Grace Sefakor Kwawu; Hintermann Kobina Mbroh; George Yiadom Osei; Bengyella Louis; John Gameli Deku; Emmanuel Senyo Kasu; Prosper Mensah; Charles Yao Agede; Cornelius Dodoo; Emmanuel Akomanin Asiamah; et al. (BMC, 2020)
Abstract Background Candida is the leading cause of vaginitis, and 75% of women have at least one episode of infection in their lives, with pregnancy being a predisposing factor. If left untreated, vulvovaginal candidiasis (VVC) can lead to chorioamnionitis with subsequent abortion, prematurity and congenital infection of the neonate. We aimed to determine the prevalence of VVC, identify the recent and most frequently occurring species of Candida in pregnant women, and determine the most effective antifungal drug of choice for treatment. Method A prospective cross-sectional study in which 176 high vaginal swab samples of consented pregnant women visiting the antenatal clinic from February 2018 to April 2018 were subjected to direct gram smear and culture for Candida isolation. Candida isolates were identified using a germ tube test and HiCrome Candida differential agar. Candida isolates were then subjected to a disk diffusion method using fluconazole (25 μg), nystatin (100 units), and voriconazole (1 μg) on Mueller-Hinton agar supplemented with 2% (w/v) glucose and 0.5 μg/ml methylene blue dye to determine the susceptibility pattern as per the guidelines of the Clinical Laboratory Standard Institute (CLSI). Chi-square analysis was used to ascertain the significant association of participants' sociodemographics and clinical presentations to VVC. A univariate logistic regression model was used to identify potential risk factors of VVC. Results The prevalence of VVC among our study participants was 30.7%. Non-albicans Candida (NAC) and Candida albicans had a prevalence of 74.1 and 25.9%, respectively. Candida glabrata was the most common species, followed by Candida albicans, Candida krusei, and Candida parapsilosis. 50.0, 18.5 and 3.7% of Candida species were susceptible to voriconazole, fluconazole and nystatin, respectively, whereas 37.0, 48.1 and 9.3% of Candida species were resistant to voriconazole, fluconazole and nystatin, respectively. The majority of isolates were susceptible dose dependent to all three antifungal agents, with voriconazole being the most efficacious antifungal agent. There was no significant association between participants' socio-demographic information and clinical presentations to VVC. Conclusion The prevalence of VVC was high in the study area. C. glabrata was found to be the most common cause of VVC among the pregnant women attending antenatal clinics, in the Ho Municipality region of Ghana. The majority of the Candida isolates were susceptible and resistant to voriconazole and fluconazole, respectively.